A facile and novel synthesis of N2-, C6-substituted pyrazolo[3,4- d ]pyrimidine-4 carboxylate derivatives as adenosine receptor antagonists - Venkatesan G. (Elsevier Masson SAS, 2016)
10.1016/j.ejmech.2015.01.046